The zombie ISDS : rebranded as ICS, rights for corporations to sue states refuse to die - Eberhardt, Pia; Ainger, Katharine (CEO; War on Want; 11.11.11, 2016)
"Author : Pia Eberhardt ; editor : Katharine Ainger"